1994
DOI: 10.1007/bf00303612
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of childhood headache

Abstract: This multicenter study reports the results obtained between 1990 and 1991 by the Study Group for Childhood Headache of the Italian Neuropediatric Society. Standardized computerized case sheets were used in order to increase the number of young patients studied and obtain more homogeneous results. A clinical diagnosis of headache was made in 600 patients (314 female and 286 male) between 4 and 12 years of age, in accordance with the classification set down by the International Headache Society. Clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Assessing pain in children is complex because few quantifiable, valid, and reliable measurement instruments exist 3‐6 . In adults, self‐report measures are currently considered to be the most reliable indicators of pain.…”
mentioning
confidence: 99%
“…Assessing pain in children is complex because few quantifiable, valid, and reliable measurement instruments exist 3‐6 . In adults, self‐report measures are currently considered to be the most reliable indicators of pain.…”
mentioning
confidence: 99%
“…These criteria offer moderate or severe Pain intensity as one possible diagnostic standard, and their use in adults has led to similar results (Silberstein and Lipton, 1993). Moreover, a recently published out-Patient study (Ferrari et al, 1994) comparing children with migraine and those with tension-type headache arrived at similar conclusions. in that study, pain was found to be more severe in children with migraine.…”
Section: Discussionmentioning
confidence: 77%